Nano-Electronic Devices Semiclassical and Quantum Transport Modeling - Vasileska, Dragica; Goodnick, Stephen M. (Springer New York : Imprint: Springer, 2011)
This book describes the state of the art in transport modeling, relevant for the simulation of nanoscale semiconductor devices. It systematically explains theoretical approaches and numerical solutions that are used in explaining the operation of both power devices and nano-scale devices. It clearly explains for what types of devices a particular method is suitable, which is the most critical point that a researcher faces and has to decide upon when modeling semiconductor devices. This book compiles different approaches to the problem of transport in mesoscopic semiconductor systems, ranging from semi-classical to fully quantum mechanical, in order to understand the advantages and limitations of each, as well as elucidating the complex and interesting phenomena encountered in ultra-small devices. .